Students’ Expectation Regarding the Presentation Learning System - Lisnawati, I (KnE Social Sciences, 2018)
The purpose of this research was to describe students’ expectations regarding the speaking learning system, especially the presentation. The method used in this research was a descriptive qualitative method. Data were obtained through questionnaires and interviews about the expectations expressed by 139 undergraduate students and two lecturers on the components in the presentation learning system. The results of the research showed that the expectation of the students with regard to different presentation learning designed and implemented by the lecturers was in terms of learning materials, instructional media, and instructional techniques. These differences were caused by the differences in the students’ and lecturers’ perceptions and the lack of communication between them. The solution to the problem was that the lecturer should redesign the components of the presentation learning system by taking into account the students’ needs. Keywords: learning components, presentation learning, students’ learning expectation